A new microcystin producing Nostoc strain discovered in broad toxicological screening of non-planktic Nostocaceae (cyanobacteria) - Kust, Andreja; Urajová, Petra; Hrouzek, Pavel; Vu, Dai Long; Čapková, Kateřina; Štenclová, Lenka; Řeháková, Klára; Kozlíková-Zapomělová, Eliška; Lepšová-Skácelová, Olga; Lukešová, Alena; Mareš, Jan (Toxicon, 2018)
Benthic cyanobacteria recognized as producers of natural products, including cyanotoxins, have been neglected for systematic toxicological studies. Thus, we have performed a broad study investigating cyanotoxin potential of 311 non-planktic nostocacean representatives combining molecular and chemical analyses. Out of these, a single strain Nostoc sp. Treb K1/5, was identified as a new microcystin producer. Microcystins [Asp3]MC-YR, [Asp3]MC-FR, [Asp3]MC-HtyR and Ala-Leu/Ile-Asp-Arg-Adda-Glu-Mdha are reported for the first time from the genus Nostoc. All the studied strains were also analyzed for the occurrence of nodularins, cylindrospermopsin and (homo)anatoxin-a, yet no novel producer has been discovered. Our findings indicate rare occurrence of the common cyanotoxins in non-planktic nostocaceae which is in contrast with frequent reports of cyanotoxin producers among phylogenetically closely related planktic cyanobacteria.
Keywords: Phylogeny; Nostoc; Cyanotoxins; Microcystin; Microcystins; Anabaena; Non-planktic Nostocaceae; mikrocystiny; Heterocytous cyanobacteria; fylogeneze